1991
DOI: 10.1002/rog.1991.29.s2.823
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Earth Materials: Six Easy Pieces

Abstract: Detailed knowledge of rheology is critical to understanding tectonic processes. Laboratory experiments to determine the strength of rocks have provided quantitative bounds on the strength of the crust and mantle. This knowledge has allowed computation of large scale deformation in the asthenosphere, given guidance in interpreting field structures, and improved our knowledge of the earthquake process. Progress has been particularly rapid in some areas: the effect of point defect chemistry on high temperature st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 809 publications
(255 reference statements)
0
4
0
1
Order By: Relevance
“…Quantitative estimates of the viscosity of the Earth's lower crust and upper mantle are based on modeling of postseismic surface deformation [ Freed and Burgmann , 2004; Hetland and Hager , 2003; Hu et al , 2004; Kenner , 2004; Nishimura and Thatcher , 2003; Vergnolle et al , 2003] and extrapolation of laboratory measurements to natural conditions [e.g., Kohlstedt et al , 1995; Montesi and Hirth , 2003]. Early experimental investigations on natural samples revealed that so‐called “dry” or anhydrous rocks are much stronger than “wet” or hydrous aggregates, see reviews by Evans and Dresen [1991] and Evans and Kohlstedt [1995]. The terms “dry” and “wet” indicate mainly the heat treatment of samples before deformation, e.g., water‐added, as‐is or untreated, oven‐dried, or vacuum‐dried, but usually without specification of water content or the type of hydrogen incorporation, e.g., as fluid inclusions or structurally bonded hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative estimates of the viscosity of the Earth's lower crust and upper mantle are based on modeling of postseismic surface deformation [ Freed and Burgmann , 2004; Hetland and Hager , 2003; Hu et al , 2004; Kenner , 2004; Nishimura and Thatcher , 2003; Vergnolle et al , 2003] and extrapolation of laboratory measurements to natural conditions [e.g., Kohlstedt et al , 1995; Montesi and Hirth , 2003]. Early experimental investigations on natural samples revealed that so‐called “dry” or anhydrous rocks are much stronger than “wet” or hydrous aggregates, see reviews by Evans and Dresen [1991] and Evans and Kohlstedt [1995]. The terms “dry” and “wet” indicate mainly the heat treatment of samples before deformation, e.g., water‐added, as‐is or untreated, oven‐dried, or vacuum‐dried, but usually without specification of water content or the type of hydrogen incorporation, e.g., as fluid inclusions or structurally bonded hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of many of the high-temperature constitutive laws is that creep rate is related to differential stress, (T, by a power law of the form, (15) where ai is the activity of the ith component, q,, n, and Qz are constants, and AZ is a weak function of T. Often experimentalists simply adopt (15) and determine n experimentally (Table 3) , the empirically determined flow law constants are, respectively, n=7.7 and 7.6 and Qx=255 and 420 kJ/mole (for deformation at strain rates of 10e3 to low6 s-' and temperatures of 500 to 1OOO'C). Thus, although there is general agreement concerning the stress exponent, activation energies for the two rocks differ significantly.…”
Section: Dislocation Creep Experimentsmentioning
confidence: 99%
“…(1) 关键词主要集中在材料的力学性能方面,如 Brittle-Ductile Transition [7-13]、Mechanical Properties [14][15][16][17][18] 、 Deformation [19][20][21][22][23][24] 、 Fracture [25][26][27][28][29][30] 、 Toughness [31][32][33][34]、Strength [33,[35][36][37][38][39]、Brittle [40][41][42][43][44][45]、 Plasticity [46][47][48][49][50][51] [110,111]。 磷元素是也钢中一种常见的微量元素,其含量一 般在 0.005%~0.04%之间 [112,113] [122,125,126] [13] Murray G T. Brittle-Ductile Transition Temperatures in Ionic Crystals [J]. Journal of the American Ceramic Society, 1960, 43(6): 330-334.…”
unclassified